Soft skills and transformational and participatory leadership of management students of a National University in Peru - Perales, Esther Jesús Vilca; Acevedo, Jesús Enrique Reyes; Hernandez, Erika Yanet Villamares; Vasquez, Uldarico Canchari (Eximia, 2022)
The purpose of the study was to determine how Soft Skills are related to the Transformational and Participatory academic leadership of the fifth year students of the Faculty of Administration - San Luis Gonzaga National University, an BASIC research was carried out, EXPLANATORY level and the design of the Research for its purpose is EX POST-FACT of a NON-EXPERIMENTAL nature, of a correlational nature. The population was made up of fifth-year students who attended the 2019-II academic semester, a total of 194 students; and the sample was 130 fifth-year A.A. 2019-II, with a confidence level of 95%, and a margin of error of 5%. The data collection techniques were observation, recording and the survey; To test the hypothesis, a 22-question questionnaire with closed-answer alternatives was applied. The results obtained the relation of both variables having at the end p value = 0.000 <0.05 and with a contingency coefficient of high intensity in the relation whose value is 0.546 and a with p value = 0.000 <0.05 (Table N ° 08 and 09), it is concluded that there is a relationship between soft skills and the transformational and participatory leadership of the fifth-year students of the Faculty of Administration of the San Luis Gonzaga National University, in 2019.